Ursodeoxycholic acid and severe COVID-19 outcomes in a cohort study using the OpenSAFELY platform - Ruth E. Costello; Karen M. J. Waller; Rachel Smith; George F. Mells; Angel Y. S. Wong; Anna Schultze; Viyaasan Mahalingasivam; Emily Herrett; Bang Zheng; Liang-Yu Lin; Brian MacKenna; Amir Mehrkar; et al. (Communications Medicine, 2024)
Abstract Background Biological evidence suggests ursodeoxycholic acid (UDCA)—a common treatment of cholestatic liver disease—may prevent severe COVID-19 outcomes. We aimed to compare the hazard of COVID-19 hospitalisation or death between UDCA users versus non-users in a population with primary biliary cholangitis (PBC) or primary sclerosing cholangitis (PSC). Methods With the approval of NHS England, we conducted a population-based cohort study using primary care records between 1 March 2020 and 31 December 2022, linked to death registration data and hospital records through the OpenSAFELY-TPP platform. Cox proportional hazards regression was used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for the association between time-varying UDCA exposure and COVID-19 related hospitalisation or death, stratified by geographical region and considering models unadjusted and fully adjusted for pre-specified confounders. Results We identify 11,305 eligible individuals, 640 were hospitalised or died with COVID-19 during follow-up, 400 (63%) events among UDCA users. After confounder adjustment, UDCA is associated with a 21% relative reduction in the hazard of COVID-19 hospitalisation or death (HR 0.79, 95% CI 0.67–0.93), consistent with an absolute risk reduction of 1.35% (95% CI 1.07%–1.69%). Conclusions We found evidence that UDCA is associated with a lower hazard of COVID-19 related hospitalisation and death, support calls for clinical trials investigating UDCA as a preventative measure for severe COVID-19 outcomes.